Relations of high sensitive C-reactive protein (hs-CRP) with microalbuminuria as a useful predictor of cardiovascular risk among type 1 diabetes mellitus patients - Abeer J. Hassan (مجلة كلية الطب, 2016)
Background: Inflammation and more specifically inflammatory cytokines are determinant in the development of microvascular diabetic complications, including neuropathy, retinopathy and nephropathy. Objective: The aim of present study is to evaluate the relationships between high sensitive C-reactive protein, microalbuminuria and risk factors for cardiovascular disease. Subjects and methods: the study involved (30) patients with type 1 diabetic mellitus compared to (30) healthy control. A fasting blood sample was drawn from all subjects after an overnight fasting to measure the biochemical parameters which including glycated hemoglobin, lipid profile, atherogenic index of plasma and high sensitive C-reactive protein concentration in blood of all subjects, also evaluating microalbuminuria, creatinine, urea level in urine of type 1 diabetic mellitus patients and healthy control. Results: results revealed a significant increase in the level of glycated hemoglobin, total cholesterol, triglyceride, low density lipoprotein, high sensitive C-reactive protein, microalbuminuria, urea and atherogenic index of plasma. While a significant decrease in high density lipoprotein level in patients group compared with control group. Also, there were a highly significant positive correlation between high sensitive C-reactive protein and glycated hemoglobin, atherogenic index of plasma and microalbuminuria. Conclusions: the results of this study suggests that high sensitive C-reactive protein can be use with microalbuminuria as a biochemical marker to predict the early stage of cardiovascular disease in children and adolescents with type 1 diabetic mellitus.